Is er een seksuele revolutie? - Sengers, W.J.; Rietdijk, C.W.; Swiebel, Joke; Fortuin, Johanna; Schapenk, A.G.W. (Rotterdam : Universitaire Pers Standaard Wetenschappelijke Uitgeverij, 1970)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie